Land suitability evaluation in the Northern Limestone Mountains of Tuban Regency, East Java for torch ginger (Etlingera elatior Smith) cultivation - Laela, Fadhilatul; Ammurabi, Syah Deva (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
Torch ginger (Etlingera elatior) is a herbaceous plant from Southeast Asia, traditionally used as herbal medicine by local people due to its antibacterial, antiviral, anti-inflammatory, anti-allergic, antioxidant, and anti-cancer properties. Despite its various benefits, this plant has struggled to enter the market because it has not been cultivated on a large scale. Therefore, the opportunity for commercial cultivation of this plant remains wide open. Tuban Regency is a potential agricultural district in Java, strategically positioned on the main road between Central Java Province and East Java Province. Unfortunately, little research has been conducted on land suitability evaluation in Tuban Regency’s agricultural areas. This research aimed to evaluate land suitability for torch ginger cultivation in Tuban Regency. Based on the studies conducted, agricultural land in Tuban Regency is quite fertile, but adequate irrigation is necessary to help the plants survive during the dry season. Torch ginger naturally grows in densely vegetated areas with sufficient water availability. Therefore, cultivating torch ginger in Tuban requires several special treatments, such as maintaining water availability, providing shade and mulch to regulate temperature and humidity, applying phosphorus and organic fertilizers to address phosphorus fixation in limestone soil, and using growth regulators like paclobutrazol to overcome flowering inhibition. From the various literature that has been studied, it was found that the land in the Northern Limestone Mountains of Tuban Regency, is quite fertile and suitable for agricultural land.